ChemInform Abstract: Enantioenriched Isoindolinones from Chiral Phase‐Transfer‐Catalyzed Intramolecular Aza‐Michael Reactions. Issue 5 (4th February 2014) - Sallio, Romain; Lebrun, Stephane; Schifano‐Faux, Nadege; Goossens, Jean‐Francois; Agbossou‐Niedercorn, Francine; Deniau, Eric; Michon, Christophe
Abstract Optimized reaction conditions including a optically active tris cinchonium catalyst are developed for the intramolecular aza‐Michael reactions of benzamide substrates to afford isoindolinones with moderate enantioselectivities.